Performances Fourragères De L’orge (Hordeum Vulgare L.), Du Triticale (X Tritico-Secale Wittmack) Et Du Pois (Pisum Sativum L.) Et De Leurs Associations Sous Conditions Semi-Arides - Benider Chafia; Bouzerzour Hamenna; Bouguendouz Abdelghani (European Scientific Journal, ESJ, 2017)
Under arid and semi-arid environments of the south Mediterranean sea, characterized by low and erratic rainfall, the use of low amount of water efficiently receipted in plant and animal production is very paramount to producers. Under such growth conditions, plant production is low and irregular because of the effect of water and heat stresses. To minimize the effect of these constraints, despite the low range of the species to be adopted, crop diversification and animal production were targeted. A study comparing forage performances of barley, triticale, and their associations with pea was undertaken during the 2015/2016 cropping season. The results showed that barley yielded best in sole crop than when intercropped with pea. Triticale intercropped with pea exhibited higher forage yield, 11% productivity gain equivalent at 6q/ha, and improved forage quality. This association could serve as an alternative to fallow reduction. These preliminary results indicated that, under semi-arid conditions, forage diversification is possible and some aspects of this diversification need to be investigated.